Investigation of cystathionine β-synthase as a cause of mild hyperhomocysteinaemia in patients with peripheral vascular disease - De Wet, Barend J M (Division of Chemical Pathology, 2017)
Hyperhomocysteinaemia is a recently established risk factor for the development of vascular disease and is caused by a variety of defects in the metabolism of methionine as well as dietary deficiencies of the vitamin cofactors (B6, B12 and folate) of the enzymes involved in methionine metabolism. Cystathionine β-synthase (CBS) is the most common genetic cause of homocystinuria, the severe form of the disease. The incidence of CBS deficiency in a group of 12 young patients of varied ethnic origin, who had peripheral vascular disease (PVD) that could not be ascribed to any of the conventional risk factors and were selected for having hyperhomocysteinaemia, either in the fasting state or after methionine load, was investigated. Nine out of the ten patients tested, showed abnormally elevated plasma homocysteine levels after methionine load, indicating a high incidence of deficient transsulfuration, which may have been caused by defects in CBS. Very wide variation in the CBS assay has hampered efforts to establish the contribution of CBS deficiency to the hyperhomocysteinaemia observed in this population. Therefore, a major part of this work has focussed on the source of this variation and the data suggests that between experiment variation as a result of changes in enzyme activity during the culture of the fibroblasts makes the biggest contribution. The most appropriate criterion to identify heterozygotes for CBS deficiency under these circumstances is to measure reduced CBS activity on several separate occasions compared to a control group. Only one of the group of 12 PVD patients (patient 1000) was identified as a heterozygote for CBS deficiency using this standard. Heterozygosity for CBS deficiency therefore seems to make only a minor contribution to the observed hyperhomocysteinaemia in this group of patients. Molecular genetic investigations were performed on selected individuals. Patient 1000 was confirmed to be a heterozygote for CBS deficiency. An A to G transition at nucleotide 695 leading to histidine to arginine substitution at amino acid 232 was found in one allele of this patient. A young homocystinuric female (patient 960) was confirmed to be compound heterozygote for CBS deficiency, with the common Celtic G₉₁₉A transition on the one allele and a novel duplication of the 7 bases between position 1553 and 1559 on the other allele. This 7bp insertion was identified as coming from the mother (patient 961). In an attempt to find an alternative or perhaps more sensitive method for the detection of defects in methionine metabolism, dual metabolic labelling of cultured fibroblasts with L-[methyl-³H]-methionine and L-[³⁵S]-methionine was developed to investigate these pathways in homozygotes and heterozygotes for CBS deficiency compared to controls. Although, no differences in the ratio of ³H/³⁵S were found that could be used to identify the zygosity of the patient for CBS deficiency, changes in the ratio of ³H/³⁵S over time in certain cellular compartments suggest that further development of this approach may prove to be useful.